Analisis Penerapan Akuntansi Aset Tetap Menurut PSAK No. 16 Tahun 2018 Pada Rumah Sakit Umum Haji Makassar - Amaliah, Musdalifah; Dunakhir, Samirah; Samsinar, Samsinar (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the implementation of fixed asset accounting at Haji General Hospital Makassar in accordance with PSAK No.16 of 2018. A descriptive qualitative method was used, with data collected through observation, documentation, and primary sources such as the 2024 fixed asset report. The analysis focused on aspects including asset recognition, initial and subsequent measurement, depreciation, and presentation in the financial statements. The results indicate that the hospital has applied fixed asset accounting in line with PSAK No.16. Assets are recognized based on expected future economic benefits and measured at reliably determined acquisition costs. The hospital adopts the cost model and consistently applies the straight-line depreciation method. Overall, the implementation of fixed asset accounting at Haji General Hospital Makassar reflects proper compliance with applicable financial reporting standards